SERVANT LEADERSHIP AMONG TEACHERS: THE INFLUENCE OF LEADER EMPATHY, ORGANIZATIONAL ETHICAL CLIMATE, AND TEAM PSYCHOLOGICAL SAFETY - Waldan, Raziki; Zarkasi, Zarkasi; Jauhari, Mohammad Mas'ud (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Servant leadership has attracted growing attention across disciplines; however, its determinants remain underexplored, particularly in the teaching profession in West Kalimantan. Teachers in this region work in culturally diverse school environments, while most previous studies have focused on corporate or urban public institutions. Research examining leader empathy, organizational ethical climate, and team psychological safety in multicultural educational contexts is still limited. This study examines the influence of leader empathy and organizational ethical climate on servant leadership among teachers, and the moderating role of team psychological safety. A quantitative survey was conducted with 112 teachers from different school levels using stratified random sampling. Data were collected through an online Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that leader empathy and organizational ethical climate have a positive, significant effect on servant leadership, whereas team psychological safety does not moderate these relationships. These findings highlight the importance of empathetic leadership and ethical organizational culture in promoting servant leadership among teachers. JEL: I21, M54, Z13.